2021
DOI: 10.1038/s41467-021-22739-3
|View full text |Cite
|
Sign up to set email alerts
|

A heterocyte glycolipid-based calibration to reconstruct past continental climate change

Abstract: Understanding Earth’s response to climate forcing in the geological past is essential to reliably predict future climate change. The reconstruction of continental climates, however, is hampered by the scarcity of universally applicable temperature proxies. Here, we show that heterocyte glycolipids (HGs) of diazotrophic heterocytous cyanobacteria occur ubiquitously in equatorial East African lakes as well as polar to tropical freshwater environments. The relative abundance of HG26 diols and keto-ols, quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…S13 ) holds in the MH, the reduced seasonality inferred from our coral records would imply warmer mean MH WP SSTs in the WIO. This is confirmed by the sediment records from the WIO and East African lakes that show substantial, sustained warming between 8 and 5 ka BP 15 , 16 , 30 , 32 . Reduced seasonality coupled with warmer mean SSTs would imply greater warming in the cold season, e.g.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…S13 ) holds in the MH, the reduced seasonality inferred from our coral records would imply warmer mean MH WP SSTs in the WIO. This is confirmed by the sediment records from the WIO and East African lakes that show substantial, sustained warming between 8 and 5 ka BP 15 , 16 , 30 , 32 . Reduced seasonality coupled with warmer mean SSTs would imply greater warming in the cold season, e.g.…”
Section: Discussionsupporting
confidence: 61%
“…This suggests that a warmer Indian Ocean will have a more uniform SST distribution and a reduced SST seasonality. We therefore believe that the reduced seasonality observed in our coral Sr/Ca records can be attributed to warmer mean temperatures in the WIO and equatorial East Africa between 8 and 5 ka BP, as inferred from sediment records covering the MH 15,16,30,32 . Furthermore, we propose that rapid warming in boreal fall driven by the fall insolation maximum raised SSTs at the start of the warm season to the upper limit of Indian Ocean SSTs under MH climatic conditions.…”
Section: Mid-holocene Temperatures In the Western Indian Ocean And Ea...mentioning
confidence: 67%
See 1 more Smart Citation
“…Similar observations have been made in cultured cyanobacteria, in which the proportion of HG diols has been found to increase with growth temperature (Bauersachs et al, 2014). The HDI 26 , a HG based proxy to reconstruct surface water temperatures (SWT) in lacustrine environments (Bauersachs et al, 2015(Bauersachs et al, , 2021, revealed substantial variations between the Antarctic meltwater ponds (HDI 26 : 0.24 -0.68, SWT: -6 -11 • C) and lakes (HDI 26 : 0.32 -0.54, SWT: -5 -5 • C) compared to the (sub)tropical mats (HDI 26 : 0.90 -0.97, SWT: 21 -23 • C). HG distribution patterns and the HDI 26 thus express a significant climate-driven component, which may compensate for varying rates of oxygen diffusion into the heterocyte with temperature variation and provide cyanobacteria with an anaerobic microenvironment to allow for biological N 2 fixation (Bauersachs et al, 2009a).…”
Section: Temperature Controls On Heterocyte Glycolipid and Bacterioho...supporting
confidence: 52%
“…We detected heterocyte glycolipids HG 26 diols and keto-ols as well as HG 28 diols and keto-ols, organic molecules consisting of a sugar functionality glycosidically bound to long carbon chains with hydroxy and/or ketone functionalities, which are exclusively synthesized by N 2 -fixing heterocytous cyanobacteria ( 16 ) that are common in freshwater. Application of the HDI 26 (heterocyte diol index of 26 carbon atoms) lipid paleothermometer ( 17 ) using a previously established modern lake surface sediment calibration ( 18 ) yielded a reconstructed summer water temperature of 18.7°C (with a calibration error of ±1.7°C) for the depositional environment.…”
Section: Resultsmentioning
confidence: 99%